EOR Screening and Optimizing Study on Carbonate Reservoirs - Mistor, Nor Suzairin (Universiti Teknologi PETRONAS, 2011)
By times, production of oil will decrease eventually. Not all the oil in the reservoirs will be produced during the process. A substantial amount of oil will remain in place or is called as residual oil saturation (Sor) due to a partial sweep of the reservoir and oil is trapping by capillary forces in the invaded zones. Therefore, researches have been developed and Enhanced Oil Recovery (EOR) is the trusted technology to improve the production and recovery in the oil fields. The objectives ofEOR are (1) to improve the sweep efficiency, by reducing the mobility ratio between injected and inplaced fluids, (2) to eliminate or reduce the capillary forces and thus improve displacement efficiency, and (3) to act on both phenomena simultaneously. Different fields acquire different methods of EOR. Hence, in order to fmd the best method, a screening process has been done. The criteria and properties of both method and reservoirs are taken into account in order to choose the exact method for the specific reservoir. The properties are based on the successful field projects and continuous research. In this project, which is focusing on the carbonate reservoirs lithology,all the EOR methods and fields properties will be screened by using two methods which are (1) manual screening and (2) by using EOR screening. EOR screening is software that has been developed by the author using the macro visual basic in Microsoft Excel2007. About 48 previous projects in carbonate reservoirs' field has been tested using this software and the result shows gas injection as the mostly suitable method for this lithology.